Medication Record Management System For Klinik Tweedie - Seethaiah, Sharnitha; Suhaila Mohd.Yasin, (Applied Information Technology And Computer Science, 2022)
Medication Record Management System is a software that assists medical staff members such as doctors, nurses, and clinic assistants in better managing their clinic, increasing clinic efficiency, integrating clinic operations, limiting clinic expenditure and staff manual work, and ultimately providing better care to patients. It is proposed for Klinik Tweedie after the clinic finds that there are several problems with the management of its medication records such as manual recording of the medicines using paperworks, no proper records are registered, and the management of the medications cannot be performed in various ways such as arranging the information chronologically or alphabetically. The objective of the project is to design a web-based medication record management system that records and manages medication data for Klinik Tweedie in order to efficiently manage the medicine information. This project involves three users namely administrator, doctor and staff respectively. Medication Record Management System for Klinik Tweedie is developed using structured approach and waterfall model development. The web-based system is cost-effective and energy-saving, also improves documentation and record keeping of medical information.